UJI KANDUNGAN KIMIA DAN CEMARAN LOGAM KERANG KIMA (Tridacna sp.) KERING YANG DIPERDAGANGKAN DI KABUPATEN KONAWE UTARA SULAWESI TENGGARA - Alam, Samsul; Isamu, Kobajashi Togo; Suwarjoyowirayatno, Suwarjoyowirayatno (Jurnal Fish Protech, 2020)
The Test of Chemical Content and Metal Contamination of Dry Clam (Tridacna sp.) Traded in North Konawe Regency Southeast SulawesiABSTRACT         The aim of this study was to determine the characteristics of chemical composition (water, ash, protein, fat, and carbohydrate) and Metal Contamination of Dry Clam. The analysis of the data used in this study is to use descriptive analysis. The results of the analysis of the chemical content of the highest treatment of water content are found in P2 with a value of 25.84%. The highest ash content was found in the P2 treatment with a value of 13.84%. The highest level of protein treatment was at P3 with a value of 14.28%. The highest treatment fat content was in P3 with a value of 2.43% and the highest treatment carbohydrate content was in P2 with a value of 1.88% and. The results of the analysis of heavy metals were the highest Cd levels were at P3 with a value of 0.074 mg / Kg and the lowest was at P1 0.057 mg / Kg and the highest Pb metal at P3 0.026 mg / Kg the lowest was at P1 0.016 mg / Kg.Keywords: Clam (Tridacna sp.), Chemical content, Heavy metals ABSTRAKTujuan penelitian ini adalah untuk mengetahui karakteristik komposisi kimiawi (air, abu, protein, lemak, dan karbohidrat) dan cemaran Logam berat pada Kerang kima Kering. Analisis data yang digunakan dalam penelitian ini adalah menggunakan analisis deskriptif. Hasil analisis kadar kimia perlakuan kadar air tertinggi terdapat pada P2 dengan nilai 25,84%. Kadar abu tertinggi terdapat pada perlakuan P2 dengan nilai 13,84%. Perlakuan protein tertinggi terdapat pada P3 dengan nilai 14,28%. Kadar lemak perlakuan tertinggi terdapat pada P3 dengan nilai 2,43% dan kadar karbohidrat perlakuan tertinggi terdapat pada P2 dengan nilai 1,88% dan. Hasil analisis logam berat kadar Cd tertinggi pada P3 dengan nilai 0,074 mg / Kg dan terendah pada P1 0,057 mg / Kg dan logam Pb tertinggi pada P3 0,026 mg / Kg, terendah pada P1. 0,016 mg / Kg.Kata kunci Kerang kima (Tridacna sp.) kering, Kandungan Kimia, Logam berat